Should we systematically test patients with clinically isolated syndrome for auto-antibodies?. (December 2015) - Negrotto, Laura; Tur, Carmen; Tintoré, Mar; Arrambide, Georgina; Sastre-Garriga, Jaume; Río, Jordi; Comabella, Manuel; Nos, Carlos; Galán, Ingrid; Vidal-Jordana, Angela; Simon, Eva; Castilló, Joaquín; et al.
Background: Several autoimmune diseases (ADs) can mimic multiple sclerosis (MS). For this reason, testing for auto-antibodies (auto-Abs) is often included in the diagnostic work-up of patients with a clinically isolated syndrome (CIS). Objective: The purpose was to study how useful it was to systematically determine antinuclear-antibodies, anti-SSA and anti-SSB in a non-selected cohort of CIS patients, regarding the identification of other ADs that could represent an alternative diagnosis. Methods: From a prospective CIS cohort, we selected 772 patients in which auto-Ab levels were tested within the first year from CIS. Baseline characteristics of auto-Ab positive and negative patients were compared. A retrospective revision of clinical records was then performed in the auto-Ab positive patients to identify those who developed ADs during follow-up. Results: One or more auto-Ab were present in 29.4% of patients. Only 1.8% of patients developed other ADs during a mean follow-up of 6.6 years. In none of these cases the concurrent AD was considered the cause of the CIS. In all cases the diagnosis of the AD resulted from the development of signs and/or symptoms suggestive of each disease. Conclusion: Antinuclear-antibodies, anti-SSA and anti-SSB should not be routinely determined in CIS patients but only in those presenting symptoms suggestive of other ADs.